2017
DOI: 10.17567/ataunidfd.307109
|View full text |Cite
|
Sign up to set email alerts
|

Bond Strength of Soft Lining Material to Polyamide Denture Material

Abstract: Aim:The aim of this study was to evaluate the bond strength of soft lining material to polyamide denture material. Materials and Methods: Twenty-five polyamide denture base materials and soft denture lining material were used in this study. The samples were divided into five groups according to the surface treatments: Group 1 (Control): No surface treatment Group 2: Samples were sandblasted with 5o µm Al 2 O 3 powder. Group 3: Samples were grinded with a diamond bur. Group 4: Samples were etched with % 37 Orth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Also, other research showed there was an improvement in the peel strength by surface treated with Al 2 O 3 or CO 2 laser, one of the factors that might affect the outcomes in laser group in different studies is the rate of scanning of the laser tip and the distance of the tip to the surface [26], the scan rate could result in different cavities on the surface of acrylic resin. The use of the laser in the focus or defocus mode might also affect the ability to create pits by the laser beams [44]. In this study in the comparison between Al 2 O 3 group and CO 2 laser group, the Al 2 O 3 had decreased value of microleakage in comparison to CO 2 laser this could be explained by the roughened acrylic denture base by laser might have pits in discontinuities manner that didn't lead to enough penetration of the liner into them that created gaps and oral fluids accumulation [11 ,45].…”
Section: Discussionmentioning
confidence: 99%
“…Also, other research showed there was an improvement in the peel strength by surface treated with Al 2 O 3 or CO 2 laser, one of the factors that might affect the outcomes in laser group in different studies is the rate of scanning of the laser tip and the distance of the tip to the surface [26], the scan rate could result in different cavities on the surface of acrylic resin. The use of the laser in the focus or defocus mode might also affect the ability to create pits by the laser beams [44]. In this study in the comparison between Al 2 O 3 group and CO 2 laser group, the Al 2 O 3 had decreased value of microleakage in comparison to CO 2 laser this could be explained by the roughened acrylic denture base by laser might have pits in discontinuities manner that didn't lead to enough penetration of the liner into them that created gaps and oral fluids accumulation [11 ,45].…”
Section: Discussionmentioning
confidence: 99%